Association of low birth weight with myopic refractive error and lower visual acuity in adulthood: results from the population-based Gutenberg Health Study (GHS). Issue 1 (15th March 2018) - Fieß, Achim; Schuster, Alexander Karl-Georg; Nickels, Stefan; Elflein, Heike M; Schulz, Andreas; Beutel, Manfred E; Blettner, Maria; Pfeiffer, Norbert
Abstract : Purpose: Low birth weight (BW) is linked to impaired organ development in childhood, including altered ocular morphological and functional development. The aim of this study was to evaluate whether low BW has long-term effects on visual acuity and refraction in adulthood. Methods: The Gutenberg Health Study is a population-based, observational cohort study in Germany, including 15 010 participants aged between 35 and 74 years. These participants were divided into three different BW groups (low: <2500 g; normal: between 2500 and 4000 g; and high: >4000 g). Best-corrected visual acuity and objective refraction were examined. We used multivariable linear regression models with adjustment for age, sex, socioeconomic status and self-reported glaucoma, age-related macular degeneration, corneal disease and cataract to assess associations between BW and the main outcome measures, best-corrected visual acuity, spherical equivalent and astigmatism. Results: Overall, 8369 participants reported their BW. In a multivariable analysis, an association for low BW with spherical equivalent (B=−0.28 per dioptre, P=0.005) and best-corrected visual acuity (B=0.02 logarithm of the minimum angle of resolution, P=0.006) compared with normal BW was observed. For participants with high BW, an association was observed with spherical equivalent (B=0.29 per dioptre, P<0.001), while none with visual acuity. Conclusions: Our data demonstrated that low BW is linked to visual acuity and refractive long-term outcomes long after childhood. Individuals with low BW are more likely to have lower visual acuity and a higher myopic refractive error in adulthood. Adults with high BW are more likely to have a more hyperopic refractive error.